PENGARUH KARAKTERISTIK PEMERINTAH DAERAH DAN TEMUAN AUDIT BPK TERHADAP KINERJA PEMERINTAH DAERAH (Studi pada Pemerintah Kabupaten/Kota di Indonesia - Hafidh Susila Sudarsana; Shiddiq Nur Rahardjo (Diponegoro Journal of Accounting, 2013)
This study aims to provide empirical evidence on effect of the characteristics of localgovernment (size, level of wealth, dependence level and government expenditures) and the auditfindings to the performance of local government. Local government performance is measured byscores on the evaluation of local government performance (EKPPD) derived from localgovernment organizers report (LPPD).Population of this research is all the district/city in Indonesia during 2010. Total thissample are 367 local government using purposive sampling. Examination of hypothesis conductedby using ordinal logistic regression (PLUM) in SPSS 19 software.Results of this study indicate that level of wealth significant positive effect on theperformance of local government districts/cities in Indonesia, to audit findings significant negativeeffect on the performance of local government districts/cities in Indonesia. While size, capitalexpenditures and level of dependence had no significant effect to the performance of localgovernment districts/cities in Indonesia.